Enhancing Academic Writing Proficiency: A Data-Driven Study on EFL Students’ Challenges and Needs - Nurhayani Nurhayani; Stenlly Sedubun (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Academic writing is an important skill but remains a challenge for students of English as a Foreign Language in higher education. This study aims to analyse the academic writing abilities of sixth-semester EFL students in terms of their language proficiency, the language problems they face, and their perceived learning needs regarding academic writing. This study employed a quantitative descriptive method involving 34 students as respondents. Data were collected via a structured questionnaire comprising multiple-choice questions, checklists, and a Likert scale. The data were analysed using descriptive statistics to illustrate trends in students’ abilities, problems, and needs. The results indicate that the majority of students are at an intermediate proficiency level, with the main challenges lying in the ability to produce analytical, coherent, and cohesive writing, as well as weaknesses in paragraph organisation and grammar. Furthermore, students demonstrated a high need for more effective academic writing learning models, particularly those emphasising the pre-writing stage and idea development. These findings highlight the importance of developing an academic writing curriculum that is student-centred and capable of integrating linguistic aspects and cognitive demands in academic writing.